Kinetics and spectroscopic analyses of syngas production from glycerol steam reforming over 15WT%Ni/85WT% alumina catalyst - Cheng, Chin Kui (2013)
Part of this project reports on the longevity of glycerol reforming into syngas, specifically the longevity of glycerol reforming over the lanthanum (La) promoted Ni/Al2O3 catalysts. The XRD results showed that the Ni particle was well-dispersed in the presence of La promoter. In addition, via the NH3-TPD analysis, it was found that the La promoter has reduced the acidity of Ni catalyst which may have explained the mitigation of carbon laydown. It was determined that the 3.0 wt% La-promoted Ni/Al2O3 catalyst possessed the largest BET specific surface area of 97 m2 ·g −1. Consequently, it yielded the best catalytic longevity performance with conversion attained more than 90%, even after 72 h of reaction duration. Significantly, it can be confirmed that the presence of CO2 during the glycerol reforming was essential in reducing carbon deposition, most likely via gasification pathway. This has ensured a stability of catalytic activity for a long reaction period (72 h)